Case Report: Cerebral leukodystrophy and the gonadal endocrinopathy: a rare but real association [version 2; referees: 2 approved] - Mohammad Humayun (F1000Research, 2018)
A 30 year old married Pakistani woman presented in January 2018 with an eight month history of progressive left sided weakness, ataxia, spasticity, underdeveloped secondary sexual characteristics and primary infertility. She was the elder sister of a 19 year old bed bound woman who was diagnosed with vanishing white matter (VWM) disease 12 months previously. The MRI scan of the brain  demonstrated diffuse leukodystrophy and her hormonal assays were significant for premature ovarian insufficiency. Results from her genetic tests demonstrated a point mutation in eukaryotic initiation factor 2B (EIF2B). Thus, she was the second confirmed case of  VWM from her  family of 12 siblings with normal parents.